The World Book Encyclopedia: Volume 4: Ci-Cz (Chicago World Book, Inc., 1992)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students
22 v. : ill. (some col.) ; World Book, Inc. a Scott Fetzer Company Chicago London Sydney Toronto
Spine title: World book The World Book Encyclopedia International LIBRARY OF CONGRESS CONTROL NUMBER 90-71848
Keywords: Encyclopedias (3GdehShYGJs; General; Encyclopedias and dictionaries